A Companion to Mester de Clerecía Poetry - Bower, Robin M.,; Desing, Matthew V., (Brill's Companions to Medieval Literatures and Cultures ;, 2024)
Mester de clerecía is the term traditionally used to designate the first generations of learned poetry in medieval Ibero-Romance dialects (the precursors of modern Castilian and other Romance languages of the Iberian Peninsula). In its time, this poetry was anything but traditional. These long poems of structured verse reappropriate the heroic past through the retelling of legends from Classical Antiquity, saints' lives, miracle stories, Biblical apocrypha, and other tales. At the same time, the poems recast the place of their authors, and learned characters within their stories, in the shifting dynamics of their thirteenth and fourteenth century present. Contributors are Pablo Ancos, Maria Cristina Balestrini, Fernando Baños Vallejo, Andrew M. Beresford, Olivier Biaggini, Martha M. Daas, Emily C. Francomano, Ryan Giles, Michelle M. Hamilton, Anthony John Lappin, Clara Pascual-Argente, Connie L. Scarborough, Donald W. Wood, and Carina Zubillaga.